Constructivist Philosophy in the Context of Merdeka Belajar - Elis Hamida; M. Thoha; Yona Christiana; Caca Andika (Institute of Advanced Knowledge and Science, 2025)
This research aims to analyze the application of constructivism philosophy in the context of Freedom of Learning in Indonesia. The specific issue raised is how constructivism philosophy can help students build their own knowledge through experience and interaction with the environment. The proposal given is to apply learning methods that are based on experience and interaction, such as project methods and discussion methods. The research method used is a qualitative method with data collection techniques through interviews and observation. The research results show that the application of constructivism philosophy can help students build their own knowledge, increase learning motivation, and develop critical thinking skills. Apart from that, this research also found that the application of constructivism philosophy can help students develop effective collaboration and communication skills. The philosophy of constructivism can be a strong foundation for implementing the concept of Freedom of Learning in Indonesia. This research can contribute to the development of more effective and efficient educational theory and practice. The results of this research can also be used as a reference for developing curricula and educational programs that are more appropriate to student needs. In the context of education in Indonesia, this research has broad implications. By applying the philosophy of constructivism, education in Indonesia can become more relevant and effective in preparing students to face the challenges of the 21st century. Therefore, this research can be a reference for educators, curriculum developers and educational policy makers to advance education in Indonesia.